Strain monitoring of cement-based materials with embedded polyvinyl alcohol - carbon nanotube (PVA-CNT) fibers (Fracture and Structural Integrity, 2017)
This article investigates the possibility of exploiting innovative polyvinyl alcohol fibers reinforced with carbon nanotubes (PVA-CNT fiber) as a strain sensor in cement mortars used in the restoration of Cultural Heritage Monuments. Two types of PVA-CNT fibers were embedded in the matrix at a short distance from the bottom of the beam and their readings were correlated with traditional sensors, e.g. strain gauges and Fiber Optic Bragg Gratings. The Electrical Resistance Change (ERC) of the embedded PVACNT fiber was in-situ monitored during four-point bending mechanical tests. For the case of coated PVA-CNT fiber, a linear correlation of the applied strain at the bottom surface of the specimen along with ERC values of the fiber was noticed for the low strain regime. For the case of incremental increasing loading – unloading loops, the coated and annealed PVA-CNT fiber gave the best results either as embedded or as ‘surface attached’ sensor that exhibited linear correlation of ERC with applied strain for the low applied strain regime as well as hysteresis loops during unloading. The article discusses their high potential to be exploited as strain/damage sensor in applications of civil engineering as well as in restoration of Monuments of Cultural Heritage.
Keywords: Cement-based materials; Sensing; FOBGs; Monitoring